A Closer Look at Child Mortality among Adivasis in India - Das, Maitreyi Bordia; Kapoor, Soumya; Nikitin, Denis (2012)
The authors use data from the National Family Health Survey 2005 to present age-specific patterns of child mortality among India's tribal (Adivasi) population. The analysis shows three clear findings. First, a disproportionately high number of child deaths are concentrated among Adivasis, especially in the 1-5 age group and in those states and districts where there is a high concentration of Adivasis. Any effort to reduce child morality in the aggregate will have to focus more squarely on lowering mortality among the Adivasis. Second, the gap in mortality between Adivasi children and the rest really appears after the age of one. In fact, before the age of one, tribal children face more or less similar odds of dying as other children. However, these odds significantly reverse later. This calls for a shift in attention from infant mortality or in general under-five mortality to factors that cause a wedge between tribal children and the rest between the ages of one and five. Third, the analysis goes contrary to the conventional narrative of poverty being the primary factor driving differences between mortality outcomes. Instead, the authors find that breaking down child mortality by age leads to a much more refined picture. Tribal status is significant even after controlling for wealth.